2021
DOI: 10.1038/s41419-021-03613-y
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and the subsequent cell death transmitting from ferroptotic cells to neighboring cells

Abstract: Ferroptosis regulated cell death due to the iron-dependent accumulation of lipid peroxide. Ferroptosis is known to constitute the pathology of ischemic diseases, neurodegenerative diseases, and steatohepatitis and also works as a suppressing mechanism against cancer. However, how ferroptotic cells affect surrounding cells remains elusive. We herein report the transfer phenomenon of lipid peroxidation and cell death from ferroptotic cells to nearby cells that are not exposed to ferroptotic inducers (FINs). Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 61 publications
0
46
0
2
Order By: Relevance
“…Benedikt Kolbrink and Friedrich Alexander von Samson-Himmelstjerna contributed equally to this work. nature [14,15], leading to pronounced kidney cell death and organ failure [3][4][5].…”
Section: Cellular and Molecular Life Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Benedikt Kolbrink and Friedrich Alexander von Samson-Himmelstjerna contributed equally to this work. nature [14,15], leading to pronounced kidney cell death and organ failure [3][4][5].…”
Section: Cellular and Molecular Life Sciencesmentioning
confidence: 99%
“…If these protective mechanisms are inactivated by pharmacological agents or in the context of pathological conditions, ferroptosis occurs, as is the case in AKI. Once activated, ferroptosis spreads to neighboring cells due to its propagative nature [ 14 , 15 ], leading to pronounced kidney cell death and organ failure [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic stroke is mainly due to insufficient blood supply to the brain caused by cerebral artery occlusion, resulting in local cerebral tissue ischemia and hypoxia. Neuronal cells in the brain tissue exhibit energy or ion pump obstacles [ 4 6 ] and rapidly develop reversible or irreversible neuronal damage; therefore, subsequent reperfusion of acute ischemic stroke is essential for neuronal cell rescue [ 7 ]. However, experimental and clinical evidence has shown that restoration of perfusion, the contradiction of increased damage in the short term, often leads to reperfusion injury [ 8 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the research of probiotic lactic acid bacteria in pigs, there are some reports on the protective activity to oxidative stress [30,38], but there is no report referring to the effect of lactic acid bacteria on iron toxicity. Although at this stage the mechanism by which LpP1-2 suppresses iron toxicity is unknown, iron-dependent cell death (ferroptosis) has been reported to be involved in various human diseases [39][40][41]. In addition, the degradation of lipid peroxide [42] and the suppression of lipid peroxide toxicity [43][44] have been pointed out to be involved in the suppression of ferroptosis.…”
Section: Physiological Effectmentioning
confidence: 99%